Pizarra digital de bajo costo basado en Wiimote y su satisfacción por el Usuario - Mamani Vilca, Ecler (2019)
Modern research shows that the interactive whiteboard is an educational tool for teachers and students, however the high cost have not been acquired in educational institutions. This article shows how to perform a whiteboard with low cost using the Nintendo Wii Remote (idea of Johnny Lee) and infrared light pencil. So it was also determined that the level of satisfaction of using PDI by users is "satisfactory", this test was performed in Abancay, Perú.